Efficacy and safety of subcutaneous immunotherapy in asthmatic children allergic to house dust mite: a meta-analysis and systematic review - Zheng, Chen; Xu, Hao; Huang, Shumin; Chen, Zhimin (Frontiers in Pediatrics, 2023)
Background: Subcutaneous immunotherapy (SCIT) has been proved to be effective and safe in adult asthma. But it is still controversial in children. Object: To evaluate the efficacy and safety of SCIT in asthmatic children with allergy to house dust mite. Method: We searched the databases of Cochrane Library, EMBASE and MEDLINE (from January 1,1990 to December 1, 2022). Two reviewers independently screened studies, extracted data and critically appraised the risk of bias. We used the Revman 5 to synthesize the effect sizes. Results: We finally selected 38 eligible studies including 21 randomized controlled trials to evaluate the efficacy and safety of SCIT and 17 observational studies to assess the safety. The results revealed that short-term asthma symptom scores were declined with a standardized mean difference (SMD) of -1.19(95% CI -1.87, -0.50) in 12 researches with high heterogeneity. Short-term asthma medication scores were decreased with SMD -1.04(95%CI -1.54, -0.54) in 12 heterogeneous researches. One study showed no significant reduction in combined symptom and medication scores without providing details. No studies we reviewed reported long-term efficacy. SCIT resulted in an obviously increased risk of adverse reactions compared with placebo. For secondary outcomes, SCIT improved life quality and reduced the numbers of annual asthma attacks and allergen-specific airway hyperreactivity, but without significant improvement in pulmonary function, asthma control or hospitalization. Conclusions: SCIT can reduce the short-term symptom scores and medication scores regardless of different treatment duration or mono/polysensitization, but with an increased incidence of local and systemic adverse effects. Further studies on pediatric asthma are needed to evaluate the long-term efficacy, and clarify the effectiveness of SCIT in specific population using mix allergen extracts or with severe asthma. Overall, it is recommended for children with mild-moderate HDM-driven allergic asthma.